Production of ACE inhibitory peptides via ultrasonic-assisted enzymatic hydrolysis of microalgal Chlorella protein: Process improvement, fractionation, identification, and in silico structure-activity relationship - Jeeraporn Pekkoh; Apiwit Kamngoen; Antira Wichaphian; May Thu Zin; Supakit Chaipoot; Kamon Yakul; Wasu Pathom-aree; Wageeporn Maneechote; Benjamas Cheirsilp; Kuan Shiong Khoo; Sirasit Srinuanpan (Future Foods)
Microalgae have gained significant traction as sustainable substitutes for conventional animal-derived proteins, demonstrating remarkable potential as reservoirs of bioactive peptides. This study investigated the application of ultrasonic-assisted enzymatic hydrolysis (UAEH) to extract protein from microalgal Chlorella biomass, with the objective of generating peptides possessing angiotensin-converting enzyme (ACE) inhibitory activity. Protein hydrolysates and peptides exhibiting a substantial degree of hydrolysis and bioactivities were achieved following the optimization of ultrasonic-assisted enzymatic hydrolysis (UAEH) under specific conditions: an Alcalase enzyme to microalgal protein loading ratio of 3 %, a hydrolysis temperature of 40 °C, and a hydrolysis duration of 10 min. Interestingly, the fractionated low molecular weight (LMW) peptides (<3 kDa) demonstrated notable levels of both ABTS radical scavenging (IC50 at 3.34 µg/mL) and ACE inhibition activities (IC50 at 2.95 µg/mL), alongside a significant abundance of essential amino acids, reaching up to 34.98 %. Q-TOF-LC-MS/MS analysis of the LMW peptides verified the appearance of active sequences, identifying up to 49 LMW fragments within the fractionated LMW peptides. More importantly, in silico structure-activity relationship analysis proved the non-toxicity of the identified LMW peptides. The result indicates a potential link between 47 LMW peptides and the inhibition of ACE activity, suggesting that microalgae protein hydrolysate and peptides could be developed into new treatments for CVD and hypertension. These findings highlight the promise of microalgae from the UAEH as a source of natural ACE inhibitors or preventative nutritional supplements.